(untitled) (MAUSAM, 1972)
In connection with the activity of the Arabian Sea monsoon, Ramage’s postulate regarding the relationship between the intensity of the heat low over West Pakistan and the monsoon rains was examined and it was found that the heat low does not contribute to the strengthening. If the low level monsoon flow. The effects of monsoon perturbations are found to extend from sea level and are therefore considered directly responsible for strengthening the low level monsoon flow. A method of Identifying the effects of perturbations of active as well as weak Arabian Sea monsoon is postulated. This brought out that active Arabian Sea monsoon is associated with two cyclonic vertices which in the mean are lacated over the Gulf of Cambay (Gujarat low) and the northern parts of east coast ’eastern low’ respectively and extend from sea level upwards affecting the wind flow practically throughout the entire troposphere. The reason for the cyclonic circulation associated with the Gujarat low not being obvious in lower tropospheric levels is discussed. The importance .of contribution to northerly meridional flow along the west coast at upper tropospheric levels by the perturbations of strong monsoon is highlighted. The strength of upper level east wind maximum over south Peninsular India is found to be less during strong than in weak monsoon. This goes against the hypothesis regarding the role of release of latent heat in causing the summer time easterly jet. The effects of perturbations of weak Arabian Sea monsoon are found to be just the reverse of those of strong monsoon. Certain aspects of the transformation of airmass over the east Arabian Sea are also discussed.